LINE: Loop Integrals Numerical Evaluation - Prisco, Renato Maria; Ronca, Jonathan; Tramontano, Francesco (The journal of high energy physics, 2025)
A bstract We present methods for the numerical evaluation of the master integrals that arise in the calculation of scattering amplitudes at higher order in perturbative quantum field theory. We follow the general strategy of solving first-order ordinary differential equations through series expansion. We have collected these procedures in an open source computer program called LINE. Boundary conditions can be provided by the user or computed internally using the method of expansion by regions. Illustrative examples are also given.